Cytokeratin 8/18 overexpression and complex formation as an indicator of GST-P positive foci transformation into hepatocellular carcinomas - Kakehashi, Anna (Toxicol Appl Pharmacol, 2009)
Screening of the proteome of microdissected glutathione S-transferase placental form (GST-P) positive foci and normal-appearing liver on anionic (Q10), and cationic (CM10) surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) ProteinChip arrays demonstrated significant overexpression of cytokeratin 8 (CK8; m/z 54,020), cytokeratin 18 (CK18; m/z 47,760), microsomal cytochrome 5A (m/z 15,224) and histone type 2 H2aa3 (m/z 15,964) in the livers of rats initiated with diethylnitrosamine (DEN) followed by 10 weeks on phenobarbital (PB) at a dose of 500 ppm. Furthermore, formation of CK8 and CK18 complexes due to CK8 phosphorylation at Ser73 and Ser431 was found to be strongly associated with promotion of hepatocarcinogenesis by PB and the development of hepatocellular carcinomas. The data were confirmed by immunohistochemistry and real-time Q-PCR and profound overexpression of CK8 and CK18 (CK8/18) proteins and mRNAs were detected in several large size GST-P positive foci and liver tumors. A strong correlation between CK8/18 positive foci development and multiplicity of hepatocellular carcinomas was further observed. Moreover, elevation of CK8/18 was strongly associated with induction of cell proliferation in GST-P positive foci and tumors. In conclusion, our data imply that CK8/18 overexpression, those two cytokeratins complex formation associated with histone type 2 H2aa3 up-regulation and intermediate filament reorganization may drive neoplastic transformation of GST-P positive foci during rat hepatocarcinogenesis leading to the formation of hepatocellular carcinomas.